STRATEGI CARDS GROUPS PADA MATERI ASTA ISWARYA - Ni Nyoman Rejeki (Pascasarjana Universitas Hindu Indonesia, 2017)
This is a classroom action research (PTK). After the data was collected, then it is analyzed with quantitative descriptive analysis. The results of data analysis show good learning achievement. This classroom action research procedure consists of 2 cycles or more, each cycle is implemented in accordance with the changes to be achieved such as what has been designed in the factors investigated to be able to see student activities in understanding cooperative learning as well as thepercentage in the Cards Groups strategy in improving learning outcomes.